Edukasi Sunat Long Skin Short Mucosa dan Perawatan Luka Pasca Sunat - Yadi Putra; Fauziah Fauziah; Nurul Sakdah; Muhammad Daud (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This community service aims to increase family knowledge about circumcision with the long skin short mucosa methods and good and proper post-circumcision wound care so that the healing process occurs quickly. The counselling method provided by lecture and question and answer and using power point media as a tool used a projector. This community service was carried out in collaboration with the Diploma III Nursing Study Program, Faculty of Health Sciences, Abulyatama University in collaboration with the Yaditama Holistic Care clinic. This activity was attended by 15 parents whose children were circumcised. Activities include filling in data on children who will be circumcised at the Yaditama Holistic clinic. The results of this service are that participants understand and understand the latest circumcision methods and the correct way of circumcision and good post-circumcision wound care. The conclusion is that education on long skin sort mucosa circumcision and post-circumcision wound care is very important and can increase participants' understanding.